O olhar do(a) professor(a) sobre o(a) aluno(a): a relevância do afeto no ambiente escolar - Silveira, Lara Pereira Lima da (Universidade Federal do Tocantins, 2022)
This text aims to reflect on the meaning of coexistence between the teacher-student, through affective relationships. We argue that the classroom should be a beneficial space for teaching and learning. We understand that respect, affection and friendship are the main components in human coexistence. The effect is visible when the educator uses this form to teach. However, it’s perceived that this affection relationship within the classroom doesn’t always happen. That said, this article proposes to discuss how the teacher develops his work in the learning environment. It is important to pay attention to various techniques of teaching, the educator must constantly guide his students, share knowledge, inform and encourage students to study and learn. As the main result of the research, a satisfactory perspective was obtained in relation to public school teaching. that applying the methods of a good affectionate relationship between teacher and students, as an encourager, managed to make the students interact and have better use in the classes taught.